Empowerment of women: an analytical study from the Islamic perspective - Ali, Muhammad Mumtaz; Solihin, Sohirin Mohammad; Haque, Muhammad Faizul (The Islamic Cultural Center, London, 2018)
Every culture and society accords women a particular position. In most cases, woman stand divided. However, Islam has placed woman relatively dignified place, which guarantees her respectable life. This paper will explore (a) the position of the woman in the Qur'an and Prophetic tradition (b) the main obstacle that exists in empowering women, which prevents them from having dignified life. (c) current situation of empowering of women. The present paper will adopt analytical approach under which, the most relevant data from the Qur'an and the Sunnah will be gathered and analyzed. The jurisprudential views of some scholars will also be analyzed, with a view to providing solution to overcome problems related to women empowerment especially in the area of education, equality and freedom for employment. Keywords: Women-Empowerment, Analysis, Quranic perspectives, Prophetic Tradition